(untitled) - Arp, Thomas R. (Fort Worth, 2001)
This book for use in grades 11 and 12, and for college freshman. It makes the study of poetry hugely enjoyable, as it should be but rarely is, for both student and teacher.
Keywords: Poetics,Poetry,Thi pháp,Thi ca; Collections,Sưu tầm